Mediation of Personal Motivation, School and Parental Self-Efficacy in the Educational Role: A post-pandemic empirical analysis - Gutiérrez Aguilar, Olger; Mollo León, Margaret; Talavera Mendoza, Fabiola; Chicaña Huanca, Sandra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Here are several influential factors in parental self-efficacy, mediated by the personal motivation of parents towards school. The modelling of structured equations of partial minimum squares for data analysis was used. The study was conducted with 446 participants, mainly women (81.2%) and men (18%) in post-Pandemic times. The study concludes that communication with the school positively influences parental self-efficacy and personal motivation, and communication with children positively influences parental self-efficacy and motivation towards school.